Vitamin K Recent Topics on the Biology and Chemistry - Kagechika, Hiroyuki; Shirakawa, Hitoshi (Biochemistry, 2022)
Vitamin K is a fat-soluble vitamin and a significant hydrophobic signaling molecule, like vitamins A and D. Besides its classical functions as a cofactor of γ-glutamyl carboxylase, which catalyzes the γ-carboxylation of vitamin K-dependent proteins, vitamin K has novel physiological and pharmacological activities that have been elucidated in the past two decades. The discovery of detailed action mechanisms of non-classical activities of vitamin K and the development of novel derivatives with unique structural and biological profiles would improve the understanding of vitamin K functions and clinical applications. This book discusses the biology and chemistry of vitamin K, which is helpful for fundamental and clinical investigations.